2020
DOI: 10.1177/0960327120964555
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic acid ameliorates sodium nitrite-induced lung and salivary gland toxicity: Impact on oxidative stress, inflammation and fibrosis

Abstract: Despite wide application of sodium nitrite (SN) as food additive, it exhibits considerable side effects on various body organs at high dose or chronic exposure. The aim of this study was to test whether Glycyrrhizic acid (GA) could ameliorate SN-induced toxicity in lung and submandibular salivary gland (SMG). A sample size of 30 adult male albino rats was randomly allocated into 3 groups. Group 1 served as control group. Rats were treated orally with 80 mg/kg of SN in group 2 or SN preceded by (15 mg/kg) GA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
(48 reference statements)
0
17
0
1
Order By: Relevance
“…Glycyrrhizic acid (GA) is the major active constituent of a Chinese herbal medicine Glycyrrhiza glabra and possesses a wide spectrum of pharmacological actions as antioxidant, anti-inflammatory, antiviral, anticancer, and antidiabetic activities 16 . Additionally, our team has recently reported its ameliorating effect on salivary gland toxicity induced by sodium nitrite 17 . In diabetes, much evidence verified the ameliorative effects of GA on associated complications 18 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizic acid (GA) is the major active constituent of a Chinese herbal medicine Glycyrrhiza glabra and possesses a wide spectrum of pharmacological actions as antioxidant, anti-inflammatory, antiviral, anticancer, and antidiabetic activities 16 . Additionally, our team has recently reported its ameliorating effect on salivary gland toxicity induced by sodium nitrite 17 . In diabetes, much evidence verified the ameliorative effects of GA on associated complications 18 – 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with NaNO2 (80 mg/kg/d, 3 mo) by oral gavage is reported to increase renal and testicular levels of pro-inflammatory cytokines (TNF-a, IL-1b, IL-6) and decrease their levels of anti-inflammatory cytokines (IL-4, IL-10) in rats (7,8). This treatment also results in increased pro-inflammatory cytokine levels (TNF-a, IL-1b) and accelerated recruitment of macrophages in lung and submandibular salivary gland of rats (9), and leads to increased serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and pro-inflammatory cytokines (TNF-a, IL-1b) in rats (10). In contrast, Justice et al (11) have shown that pro-inflammatory cytokine levels (IL-1b, IFN-g, TNF-a) are markedly increased in quadriceps of old mice (age 20-24 mo) compared with young animals (3 mo), but are reduced to young levels by oral consumption of NaNO2 (6.656 2.1 mg/kg/d, 8 wk).…”
mentioning
confidence: 97%
“…Продукти метаболізму NO також мають неоднозначний вплив на організм. Так, надмірне надходження нітриту натрію призводить до розвитку ушкодження легенів і слинних залоз шляхом ініціації розвитку оксидативного стресу і запалення з подальшим розвитком фіброзних змін в цих органах [3]. Також нітрит натрію призводить до утворення метгемоглобіну і здатний активувати процеси перекисного окислення ліпідів в мембрані еритроцитів [4].…”
Section: вступunclassified